Electroacupuncture Reduces Oocyte Number and Maintains Vascular Barrier Against Ovarian Hyperstimulation Syndrome by Regulating CD200 - Chen, Li; Huang, Xuan; Wang, Li; Wang, Cencen; Tang, Xu; Gu, Minghui; Jing, Jun; Ma, Rujun; Ge, Xie; Yao, Bing (Frontiers in Cell and Developmental Biology, 2021)
Ovarian hyperstimulation syndrome (OHSS) is a common complication caused by ovulatory stimulation therapy, which manifests as an increase in ovarian volume, an increase in the number of oocytes retrieved, and increased vascular permeability throughout the body and especially in ovarian tissue. In our previous study, we found that electroacupuncture (EA) could prevent the development of OHSS, and the main effector is the ovary. However, we do not know the specific molecules and the mechanism of the effector. Then, OHSS rat model and EA treatment were established and the proteomic analysis of ovaries was performed. Here, CD200 was identified and significantly highly expressed in ovaries treated with EA. Clinical data showed that CD200 levels in follicular fluid were negatively correlated with the number of oocytes retrieved and serum E2. In vitro, Human chorionic gonadotropin (hCG) reduces the expression of CD200 and CD200R, increases inflammatory cytokine levels in cultured KGN cells in a concentration-dependent manner. In human umbilical vein endothelial cells (HUVECs), the vascular barrier was improved when CM (cultural medium from KGN cell) treated with CD200Fc (CD200R agonist). Meanwhile, the results of animal experiments indicated that EA reduced the number of ovarian corpora lutea and decreased inflammatory response and improved the vascular barrier function by increasing the expression of ovarian CD200 and CD200R. These findings suggest that EA treatment may reduce oocyte number and maintain vascular barrier against ovarian hyperstimulation syndrome through ovarian CD200 mediated anti-inflammatory response. Therefore, this study is the first to screen the effector molecule CD200 of EA in the ovary and elucidate the possible mechanism of EA on preventing and treating OHSS, which provide a scientific basis for CD200 as an effector target in EA treatment.